E-020 Between a Rock and a Hard Place: The Use of Self-expanding Stents for the Endovascular Treatment of Acute Ischemic Stroke due to Recalcitrant Emergency Large Vessel Occlusion in the Era of Stent-retrievers: Single-center Experience and Early Results. (29th July 2016) - Lozano, J; Howk, M; Kuhn, A; Massari, F; de Macedo Rodrigues, K; Brooks, C; Perras, M; Gounis, M; Rex, D; Wakhloo, A; Puri, A
Abstract : Objective: The efficacy of stent-retrievers in achieving recanalization in the setting of acute ischemic stroke (AIS) secondary to an emergency large vessel occlusion (ELVO) has now been conclusively proven in several randomized clinical trials. However, in a small subset of these patients recanalization may not be achieved by means of mechanical thrombectomy with stent-retrievers and/or thromboaspiration with large bore catheters. In selected cases of this type of recalcitrant occlusion, acute intracranial stenting may be safe and effective as a last and final effort to achieve flow restoration and improve recanalization rates with good clinical outcomes (Modified Ranking Scale (mRS) ≤2). Methods: Retrospective analysis of 7 patients who underwent endovascular treatment of ELVO between January 2012 and April 2016 at a single tertiary care center with acute intracranial stenting for a vessel occlusion recalcitrant to recanalization by means of standard mechanical thrombectomy and/or thromboaspiration techniques. Results: Six males and a female with median baseline National Institutes of Health Stroke Scale (NIHSS) score of 20 (range 18–29) were included in this study. Three occlusive lesions were located from the internal carotid artery (ICA) terminus to the M1, 2 lesions were distal M1 occlusions, 1 lesion was a distal M1 occlusion that spanned the superior and inferior M2 divisions, and 1 lesion was at the distal basilar extending to the bilateral P1 segments. The median number of attempted yet unsuccessful mechanical thrombectomies before considering acute intracranial stenting was 4. One procedure included balloon angioplasty prior to stenting, two procedures included mechanical thromboaspiration in addition to mechanical thrombectomy with stent-retrievers, and one of the procedures included intra-arterial TPA and thromboaspiration in between stent-retriever attempts. Two cases required Y-stenting due to recalcitrant clot burden at the bifurcation of a large vessel (MCA bifurcation into superior and inferior M2 divisions, and distal basilar artery into bilateral P1 segments; mRS at 30 days was 0 and 1, respectively). The average time from last seen well to recanalization with acute intracranial stenting was 317 min + 187 min. Recanalization rates were AOL 2 in 85% (6/7) and AOL 3 in 15% of cases (1/7). Reperfusion rates were TICI 3 in one case, TICI 2 B in 4 and TICI 2 A in 2 cases. Supraselective intra-arterial eptafibatide was used either before or immediately after stenting in 42% of cases (3/7); daily aspirin after stenting was used in all cases (7/7); and a combination of aspirin and clopidogrel was used in 71% of cases (5/7). There were two deaths: One as a result of hemorrhagic transformation of the ischemic stroke with subsequent malignant edema and the second one due to progression of stroke and withdrawal of care at the request of the family. Modified Rankin Scale mRS ≤2 at 30 days was achieved in 42% of the cases (3/7). Conclusion: Initial results suggest that acute intracranial stenting may be beneficial in a subset of patients who present with an ELVO and who have failed recanalization by means of mechanical thrombectomy with stent-retrievers and/or thromboaspiration with large bore intracranial catheters. Disclosures: J. Lozano: None. M. Howk: None. A. Kuhn: None. F. Massari: None. K. de Macedo Rodrigues: None. C. Brooks: None. M. Perras: None. M. Gounis: 1; C; NIH, Medtronic Neurovascular, Microvention/Terumo, Cerevasc LLC, Gentuity, Codman Neurovascular, Phillips Healthcare, Stryker Neurovascular, Tay Sachs Foundation, InNeuroCo Inc. 2; C; Codman Neurovascular, Stryker Neurovascular. 4; C; InNeuroCo Inc. D. Rex: None. A. Wakhloo: 1; C; NIH, Phillips Healthcare, Wyss Institute. 2; C; Codman Neurovascular, Stryker Neurovascular. 3; C; Harvard Postgraduate Course. 4; C; InNeuroCo Inc., EpiEb, Pulsar Medical. A. Puri: 1; C; Stryker Neurovascular, Covidien. 2; C; Codman Neurovascular, Stryker Neurovascular, Covidien. 3; C; Miami Cardiovascular Institute. 4; C; InNeuroCo Inc.